Eptesicus nilssonii - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
197. Northern Serotine Eptesicus nilssonii French: Sérotine de Nilsson / German: Nordfledermaus / Spanish: Murciélago hortelano nortefo Other common names: Northern Bat Taxonomy. Vesperus nilssonii Keyserling & Blasius, 1839, Sweden. Eptesicus milssonii appears to be sister to E. serotinus, and they are often paraphyletic in genetic studies using mitochondrial genes due to extensive ancient hybridization. Nevertheless, when using nuclear genes, LE. nmilssonu forms a monophyletic clade not closely related to E. serotinus. Eplesicus nilssonii 1s sometimes considered to include E. japonensis, but they are generally recognized as distinct species based on morphological data. Eptesicus gobiensis has often been included under E. nilssonii, but it is usually considered a distinct species now based on genetic and morphological distinctions. There is also considerably uncertainty as to whether the north Indian endemic E. tate: represents a distinct species or a subspecies of E. nilssonii, although it is geographically well separated from E. nilssonii and is considered a distinct species here. Distribution of E. nilssonii has been reported differently in a number of sources, making actual distribution somewhat uncertain, and distribution here should be considered as tentative. Two subspecies (nilssonii and parvus) are usually recognized, but genetic data do not support this view because there is low genetic variability between these two taxa. Monotypic. Distribution. E France to N Europe well above the Arctic Circle in Norway, Sweden, and Finland, Central Europe, Caucasus, NW Iran, and Central Asia (including N Kazakhstan) through Russia and N Mongolia to Russian Far East including Sakhalin I and Kamchatka Peninsula and S through Amur region into NC & NE China (Inner Mongolia [= Nei Mongol], Heilongjiang, Jilin, and Shandong) and Korean Peninsula, including Hokkaido and Okushirito inJapan and Kuril Is (Kunashir and Iturup); there are occasionally vagrant records throughout Europe as far S as Bulgaria and Italy and ...